(3GdJMHjQ dEjVGM eYGfi GdJjSjQs - (3eMeO Hf ESeGYjd Hf UdGM Hf eMeO GdMSfj, GdcMdGfj Ke GdUfYGfj, CHh EHQGgje, YR GdOjf, GdeYQha cCSdGag HGdCejQ, J (B1182 (3g` s; (3YHO GdQMef Hf Ydj Hf eMeO GdTjHGfqj GdRHjOj GdTGaYqj, hLjg GdOjf, GdeYQha H` GHf GdnqOrjnHY,J (B944 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi jSQ TQM CMGOjK GdQHY GdChd ef GdJjSjQ hHYO agPG TQhY ai TQM CMGOjK GdLRA GdfGSfi hHjGf VHW CdaGXg hEjVGM GdeYGfi s
(3BNQgG (B:s
(3bGdhG JaSjQ djdI GdbOQ CfgG NjQ ef Cda TgQ , ceG hQO ai GdbQBf adjQGLY ai eMdg , hGddg CYde HGdUhGH hdjcf gPG BNQ cJGH GdJMHjQ s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3HghGeTgG JYdjbGJs
(3hLGeY GdCUhd gh dCHi GdSYGOGJ eMeO Hf eMeO GHf GdCKjQ GdeJhai (B606(3g` s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B318 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B159s
Keywords: (3GdJaSjQ hYdhe GdbQBfs